2020
DOI: 10.1016/j.chb.2020.106395
|View full text |Cite
|
Sign up to set email alerts
|

Do selfie-expectancies and social appearance anxiety predict adolescents’ problematic social media use?

Abstract: In contemporary society, social media use has become a widespread daily activity, especially among adolescents, who are often engaged in visual content sharing. Taking and posting selfies on social media is one of the most popular activities associated with teens' social media use, representing a useful tool to increase their self-presentation via others' approval. However, higher exposure to visual content on social media might lead to more social comparisons and appearance concerns reinforcement. Therefore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 88 publications
(72 citation statements)
references
References 104 publications
5
60
0
7
Order By: Relevance
“…However, a larger proportion of girls (40%) than boys (28%) belonged to the group with a moderate risk for problematic use, indicating a need to pay special attention to girls in attempts to prevent problematic social media behaviour. Research has shown that several social media behaviours, such as selfie behaviour, are typical of both genders, but that for instance appearance concerns explain problematic social media use only among boys [ 49 ]. This highlights the need to study in detail the gender differences in social media use and the patterns explaining them.…”
Section: Discussionmentioning
confidence: 99%
“…However, a larger proportion of girls (40%) than boys (28%) belonged to the group with a moderate risk for problematic use, indicating a need to pay special attention to girls in attempts to prevent problematic social media behaviour. Research has shown that several social media behaviours, such as selfie behaviour, are typical of both genders, but that for instance appearance concerns explain problematic social media use only among boys [ 49 ]. This highlights the need to study in detail the gender differences in social media use and the patterns explaining them.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, how individuals cope with loneliness during forced isolation is important to the debate ( 48 , 49 ). Within this context, the use of digital technologies, and particularly social media, may serve connective functions in helping individuals to increase their social capital ( 50 , 51 ). Social media refers to producing, receiving, and sharing online content, including a wide range of Internet-related communication and social applications, such as online virtual games, blogs, e-health forums, and social networking sites.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, psychological outcomes should be considered depending on the healthy or unhealthy use of online communication and relationships. Accordingly, Baym and Ledbetter ( 65 ) already posited a strict association between the quality of relationship with SNS friends and the frequency of SNS contacts, as well as scientific research has increasingly explored the strong relationship between Internet use/misuse and interpersonal facets of Internet applications [e.g., ( 42 , 66 71 )].…”
Section: Introductionmentioning
confidence: 99%